(untitled) (Development Service Industry Management, 2024)
In the reproduction system, investments play the most important role in restoring and increasing production resources. The question of investments is especially acute during the crisis state of the country’s economy and in the conditions of transformational changes, in the conditions of the inability of enterprises to generate profit, which is one of the main sources of the formation of investment resources of the enterprise. To receive attractive investment resources, the enterprise must meet several characteristics, that is, be attractive for investment. In this regard, the use of a complex approach to the assessment of investment activity becomes important. In the process of forming a market economic system, a necessary condition for the formation of a stable position and development of an enterprise is its effective investment activity. This allows moving the financial resources of economic entities and, through their effective use, ensure the continuity of the process of production and sale of goods and services on the basis of constant renewal and expansion. Investment in the company’s activities is an objective process that develops according to its own laws and plays an important role in the development of the economy. Business entities are forced to make decisions about attracting financial resources in the form of investments to strengthen the economic security of enterprises and overcome financial problems. The growth of investment activity of the enterprise demonstrates the good financial condition of economic entities and is also a positive signal about the state of the economy and provides information about its development. The economic growth of states is largely ensured by the level of development of scientific, technical and innovative activities in all spheres of the economy, and mainly in industry. The share of new or improved technologies, products, and equipment in developed countries is from 70 to 85% of the growth of the gross domestic product. The possibilities of development, implementation and use of new and advanced technologies and products depend on the state of the investment climate in the country, the volume and structure of investments. Today, more than ever, Ukraine needs investments for economic development. Effective investment activity of industrial enterprises makes it possible to accelerate the pace of reproduction of production facilities. In turn, this process depends on the correct organization of investment activities and investment decisions.